Ecriture feminine: feminism and nationalism in Seyyedeh Zahra Hosseini’s ‘One Woman’s War: Da’ - Zeiny, Esmaeil (Penerbit Universiti Kebangsaan Malaysia, 2019)
For centuries, the tradition of veiling and public silence repressed the Iranian women both physically and verbally. These conventions stipulated that women’s physique should be concealed and their voice, emotion and concern remain unexpressed. Although Iranian women have always played crucial and representative roles in various political and historical eras, the tendency to trivialize and neglect their roles and movements has been rife. This affected Persian literature as well; women were either totally excluded or were marginalized and mentioned very briefly in literature. The Iranian women had challenged these conventions, ventured into the public, and voiced their thoughts and concerns through literature but they were again marginalized and their literature was overlooked due to possessing traditional masculine styles of writing. This sentiment gradually disappeared with the emergence of women authors whose literary works had a different style than men’s writings. These writings brought women from the periphery to the center as well. Since then, Iranian women authors have been producing literature to protest against patriarchy and traditional discriminatory policies. They have also been active writers in what now can be regarded as the formerly male-dominated genres that deal with nationalism such as war literature. ‘One Woman’s War: Da’ (2014) is one such work. Drawing upon and reviving Cixous’ notion of ecriture feminine, this paper explores how Da, a state-sponsored war memoir, constructs feminine writing that challenges patrilineal culture and highlights women’s roles in nation-building projects like the Iran-Iraq war.